Adaptive Sliding-Mode Control of an Innovative Engine Cooling System. Issue 18 (2016) - Butt, Saif S.; Prabel, Robert; Zhang, Jisheng; Aschemann, Harald
Abstract: This paper proposes a novel adaptive sliding-mode control for an innovative engine cooling system under the influence of both matched and mismatched lumped disturbances. The parameter update laws resemble a nonlinear reduced-order disturbance observer and guarantee the convergence of the estimated parameter values to the real ones. Experiments on a dedicated test rig highlight the effectiveness of the proposed novel adaptive sliding-mode control in terms of asymptotic tracking, global stability and guaranteed parameter convergence. The closed-loop stability of the overall system is established by using Lyapunov's direct method. To provide a fair comparison, the performance of the proposed controller is compared with a PI-controller.